Instrumental learning in a mouse model for obsessive-compulsive disorder: Impaired habit formation in Sapap3 mutants - Ehmer, I.; Feenstra, M.; Willuhn, I.; Denys, D. (Neurobiology of learning and memory, 2020)
It has been hypothesized that maladaptive habit formation contributes to compulsivity in psychiatric disorders such as obsessive-compulsive disorder (OCD). Here, we used an established animal model of OCD, Sapap3 knockout mice (SAPAP3−/−), to investigate the balance of goal-directed and habitual behavior in compulsive individuals and if altered habit formation is associated with compulsive-like behavior. We subjected 24 SAPAP3−/− and 24 wildtype littermates (WT) to two different schedules of reinforcement in a within-subjects design: a random-ratio (RR) schedule to promote goal-directedness, and a random-interval (RI) schedule, known to facilitate habitual responding. SAPAP3−/− acquired responding under both schedules, but showed lower response rates and fewer attempts to collect food pellets than WT, indicative of altered reward processing. As expected, WT were sensitive to sensory-specific satiety (outcome devaluation) following RR training, but not RI training, demonstrating schedule-specific acquisition of goal-directed and habitual responding, respectively. In contrast, SAPAP3−/− were sensitive to outcome devaluation after both RR and RI training, suggesting decreased engagement of a habitual response strategy. No linear relation was observed between increased grooming and behavior during the outcome devaluation test in SAPAP3−/−. Together, our findings demonstrate altered reward processing and impaired habit learning in SAPAP3−/−. We report a diminished propensity to form habits in these mice, which albeit inconsistent with the predominant idea of excessive habit formation in OCD, nonetheless points at dysregulation of behavioral automation in the context of compulsivity. Thus, the habit hypothesis of compulsivity should be updated to state that an imbalance of habitual and goal-directed responding in either direction can contribute to the development of compulsive behavior.